Inner Circle Ideology Domination in a National Commercial EFL Textbook: A Case of Indonesian Islamic-affiliated Schools - Farah, Rafika Rabba; Jarum, Jarum; Sukarma, Sukarma; Nurrofi, Rifan (Universitas Muhammadiyah Yogyakarta, 2000)
This study employs an analysis of visual images in English textbooks used in Islamic-affiliated schools through the lens of Kachru’s three-circle model of English, which categorizes English-speaking countries into Inner, Outer, and Expanding circles. This study aims to explore how these images reflect and reinforce linguistic and cultural ideologies associated with each circle. A qualitative content analysis was implemented, focusing on the visual images within English textbooks, which were categorized based on the representation of cultural elements. Data analysis was implemented using a coding scheme and Critical Discourse Analysis framework, examining the power relations and ideological influences represented by the visual content of the textbook. Results show that inner circle culture was dominantly represented (67.9%) in the textbook of its visual use. Western-looking people, outfits, movies, and food represent the images used in the textbook. The finding suggests that textbooks used in English teaching at Islamic affiliated schools, or madrasas, must be carefully designed and selected to adjust students’ needs and school context, as teaching a foreign language can carry others’ ideologies and power.